Effect of decompression and online transmission on the dimensional changes of .stl files generated by intra-oral scanning - Juliano Martins Bueno; Carolina Guarniéri Gouveia; Mayara Barbosa Viandelli Mundim; Ademir Franco; José Luiz Cintra Junqueira; Monikelly do Carmo Chagas Nascimento (PLoS ONE, 2022)
Intraoral scans became part of the virtual planning in Dentistry. In the new scenario of digital workflows, dental clinics and laboratories had to establish an online communication that requires the compression, decompression, and transmission of 3D files. Knowledge about the effects of these procedures on the dimensional properties of the files is fundamental to ensure a more realistic virtual planning. The aim of this study was to assess the influence of 3D file compression, decompression, and online transmission on the dimensional properties of dental models from intraoral scanning. Intraoral scan files in.stl format of 50 patients were selected from the database of a dental radiology clinic, with 25 of these patients with mixed dentition and 25 with permanent dentition. The maxilla and mandible scans of each patient were included in the study, generating a total of 100 files. A folder with the 100 files was created and replicated six times with different labels (A, B, C, D, E, F), totaling a sample number of 600 files. Folder A was compressed by WinZip and then decompressed. Folder B went through the same process, but the step of compression and decompression by WinZip was repeated 10 times. The folders C, D, E, F were sent, respectively, through the platforms WeTransfer, Dropbox, Google Drive, and OneDrive, then each of them was downloaded in their respective platforms. After the six folders went through the compression process and were sent by the platforms, each file in the folder was compared with its original file by superimposing the 3D images and identifying the dimensional deviation in the compressed file in relation to the original file. We observed that there were no differences between the six groups regarding dimensional changes from the compression, decompression and online transmission processes. The lack of dimensional changes was observed for the sets of permanent and deciduous. teeth We concluded that it is possible to compress, decompress, and transfer.stl format files online without causing dimensional distortions in the 3D model.